Buddhist Ethics and Development Wisdom: Buddhist Ethics and Development Wisdom - Thitsaro (Prom Khot), PhraphatPhokhin; Wongpornpavan, Chakkapan (Journal of Graduate MCU KhonKaen Campus, 2022)
Buddhist ethics uses three principles to develop wisdom as 1. Physical development is an organic development within the body is the eye, ear, nose, tongue, body and mind, which is used for connection or is connected to the outside world, including a sound, smell, taste, touch, emotion, mind awareness open the channels associated with the physical environment, and all natural. Physical development, it is organic the practice is an organic wary, so it is the strength of the canon to support mental energy security and a way to grow towards the highest wisdom 2. Canon development is the Self-training which called for training or practice in the conduct highly, or training to conduct physical, verbal order to support not persecuted. Do not destroy themselves and others as the basis of training the mind and passion is light crude down. With control wary as a basis to develop their own lives to be ready to support a charity fair at all. Especially is the basis for the development of the mind to a higher morality. And 3. Mental development is the spiritual development or contemplative development in a threefold training by focusing on the development wisdom of mental dysfunction include incorporating mindfulness and right concentration. Access to trained mental or development wisdom, and strengthen their well-established firm control with a high concentration are encouraged to mental calm, cheerful, happy, innocent, free from interference, or sad In conditions suitable for most applications. In particular, the profound wisdom, and corresponded with reality.